2013
DOI: 10.1136/archdischild-2012-303025
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting outcome in children with snake envenomation: a prospective observational study

Abstract: Objectives To evaluate clinical outcome and factors affecting outcome in children with snake envenomation. Design Prospective observational study. Setting Paediatric intensive care unit of a tertiary care teaching hospital in India. Patients We prospectively enrolled children ≤12 years of age admitted to our hospital with a definitive history of snake bite from August 2007 to June 2010. Measurements and Main Results Demographic characteristics and clinical course of the enrolled children were recorded in a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 12 publications
5
18
3
Order By: Relevance
“…The clinical features and complications noted in our sample are comparable with the findings from previous studies in children and adults 3 8 9…”
Section: Discussionsupporting
confidence: 89%
“…The clinical features and complications noted in our sample are comparable with the findings from previous studies in children and adults 3 8 9…”
Section: Discussionsupporting
confidence: 89%
“…This correlates with various studies with higher incidence in males. This is consistent with various adult as well as pediatric studies with69% males in study by Sankar et al, 68% males by Schulte et al, 60.55% males and male to female ratio of 1.5:1 by Halesha B.R et al [7][8][9] . Lower extremity is the most commonly bitten site and is comparable to other studies around 70 to 80% 6,9-12 .…”
Section: Discussionsupporting
confidence: 78%
“…Age, coagulation abnormalities, low haemoglobin, leukocytosis, thrombocytopenia and delays to treatment are all correlated with adverse outcomes in the Asian and North American viper species. [8,11,12,21,22] It is notable that acute kidney injury is a significant factor in Indian snakebites, while we found no correlation with severity and in our setting acute kidney injury is seldom reported. [16,18,19] One study from southern India reported acute kidney injury in 28% of snakebite patients, with a significant association with mortality.…”
Section: Discussioncontrasting
confidence: 69%